FIRST SIGNS, CONSEQUENCES AND PREVENTIVE MEASURES OF RADIATION OF WORKERS AT URANIUM MINES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
In this article on the basis of scientific sources the exposure of workers of uranium mines to ionizing radiation, biological effects of radiation on the body, its initial clinical signs, long-term consequences and preventive measures are analyzed on the basis of scientific sources. In the process of uranium mining, workers are exposed to alpha, beta and gamma radiation, as well as the radioactive gas - radon. These factors can cause changes at the molecular and genetic levels in the cells of the body. In the course of the study, international and domestic scientific sources on radiation hygiene, radiobiology and occupational hygiene were studied. The results of the analysis showed that compliance with radiation safety rules, the introduction of an effective ventilation system at the mines and regular medical examinations of workers significantly reduce the harmful effects of radiation.